ACCOMPANIMENT APPLICATION OF MUZARA’AH CONTRACT IN COFFEE PLANTATION AREA BETWEEN FOREST MANAGEMENT UNIT (KPH) OF PERHUTANI COMPANY JEMBER AND MULYOREJO VILLAGE - Rahmadi Indra Tektona (LP2M Universitas Ibrahimy, 2023)
Muslims are prohibited from carrying out economic muamalah activities in any field without knowledge about muamalah. Muzara'ah is an agricultural processing cooperation between the land owner and cultivator, the land owner gives agricultural land to the cultivator to be planted and maintained in return for a certain share (percentage) of the crop. Farmers who have been working as farmers for a long time, the availability of land, and the application of coffee agroforestry with the muzara'ah concept are expected to be able to improve the economy in farmer families. Unlike the case with farmers who initially did not have a job or became agricultural laborers, the existence of former forest land and the application of agroforestry are considered capable of providing opportunities to work and generate income. The research area or location chosen is in Mulyorejo Village, Silo District, Jember Regency, East Java. This decision was made with the consideration that Mulyorejo Village has experienced forest conversion into coffee-based agroforestry land and is currently experiencing conflict-prone areas. The research method used is Community development with a case study approach, counseling, training, and mentoring methods. The paper shows that the partnership agreement in the muzara'ah contract in coffee plantation area is an effort to provide legal certainty guarantees for partnering parties which in turn can improve the socio-economic for the people of Mulyorejo village and provide benefits for Perhutani KPH Jember and Jember Regency.